Analisis Perilaku Balok Kastella Dengan Variasi Jenis Bukaan - Richard Frans (Borneo Engineering : Jurnal Teknik Sipil, 2020)
The main advantage of castellated beam is the increasing of bending capacity caused by the increasing of inertia moment of steel section due to the increasing of depth of the steel section. In addition, some people argue that the opening section of castellated beam become an additional advantage in terms of aesthetics view. In general, there are three opening variations that are very often used in construction, which are hexagonal opening, circular opening, and diamond opening. Many researches have been done to compare the performance of castellated beam with various opening but only focusing on the behavior of castellated beam subjected to monotonic loading. Therefore, in this research, a review of the behavior of castellated beam with various opening subjected to quasi-static cyclic loading was carried out in order to find out which is better performance from the opening variations. A finite element analysis was conducted to find out the behavior of castellated beam with three variations of opening. A simple beam subjected to quasi-static loading using displacement control technique was considered in this research. The result shows that the castellated beam with diamond opening has a better performance compared to the other openings (hexagonal opening and circular opening).